2020 International Conference on Applications and Techniques in Cyber Intelligence Applications and Techniques in Cyber Intelligence (ATCI 2020) - Abawajy, Jemal H.; Choo, Kim-Kwang Raymond; Xu, Zheng; Atiquzzaman, Mohammed; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This book presents innovative ideas, cutting-edge findings, and novel techniques, methods, and applications in a broad range of cybersecurity and cyberthreat intelligence areas. As our society becomes smarter, there is a corresponding need to secure our cyberfuture. The book describes approaches and findings that are of interest to business professionals and governments seeking to secure our data and underpin infrastructures, as well as to individual users. .
Combination of Information Technology and College English in the Age of Media -- The Application of Computer Internet of Things in Modern Agricultural Planting Management -- The Influencing Factors Analysis of Network Interactive Teaching Mode Validity -- The Application Analysis of Computer Network Security Data Encryption Technology -- The Application of Computer Technology in Sports Training and Competition -- The Application of BIM Technology in Landscape Garden Engineering Projects -- College Physical Education Based on Multimedia Network Teaching Platform -- Development and Implementation of Health Information Management Platform in Medical Institutions -- Teaching Methods of University Economic Management Course Based on Python -- Innovative Application Paths of Big Data of Automobile Based on Internet of Vehicles.
Keywords: Engineering$1 (BData processing.s; Computational intelligence; Data Engineering; Computational Intelligence